Overview of High Fluorescence Ratio (HFR), Middle Fluorescence Ratio (MFR), Mean Cell Volume (MCV), and Mean Cell Hemoglobin (MCH) in Patients with Hemoglobin Levels Below 8 - Lestari, Nurul Wahidah; Mastiadji, Bekti (INDOGENIUS, 2025)
Background & Objective: Anemia occurs when a person has a deficiency of red blood cells or hemoglobin, with the threshold for anemia defined as hemoglobin levels below 12 g/dl. This condition is commonly found in medical practice, especially anemia caused by iron deficiency, vitamin B12 deficiency, folate deficiency, chronic disease, or bleeding. This study aimed to describe the high fluorescence ratio (HFR), middle fluorescence ratio (MFR), mean cell volume (MCV), and mean cell hemoglobin (MCH) in patients with hemoglobin levels below 8. Method: This was a descriptive study using purposive sampling, with a total of 30 respondents. Result: The results showed that 9 patients (30%) had high HFR and MFR with normal MCV and MCH; 6 patients (20%) had normal HFR and MFR with normal MCV and MCH; 5 patients (17%) had high HFR and MFR with low MCV and MCH; 3 patients (10%) had high HFR, normal MFR, and low MCV and MCH; 2 patients (7%) had high HFR and MFR with normal MCV and low MCH; 2 patients (7%) had normal HFR and MFR with low MCV and normal MCH; 1 patient (3%) had normal HFR and MFR with low MCV and MCH; 1 patient (3%) had normal HFR, high MFR, with low MCV and normal MCH; and 1 patient (3%) had normal HFR, low MFR, and normal MCV and MCH. Conclusion: This study indicates that most patients with severe anemia (Hb < 8) showed a relatively good regenerative response (as indicated by high HFR and MFR), although variations in anemia types were also observed based on MCV and MCH values, reflecting possible different causes and classifications of anemia.